Malathion, an organophosphate insecticide, provokes metabolic, histopathologic and molecular disorders in liver and kidney in prepubertal male mice. (2018) - Selmi, Slimen; Rtibi, Kais; Grami, Dhekra; Sebai, Hichem; Marzouki, Lamjed
Graphical abstract: Highlights: Malathion treatment clearly induced kidney and liver dysfunction. Malathion induced hepatic and renal changes on mRNA expressions of GPx iso-enzymes. This disruption and genotoxicity lead to histopathologic changes in liver and kidney tissues. OPs pesticides exposure lead to metabolic, histopathologic and molecular changes witch may be related to oxidative damage. Abstract: The present study was undertaken to determine the effects of malathion exposure on oxidative stress, functional and metabolic parameters in kidney and liver of prepubertal male mice. For this reason, two separated groups of prepubertal male mice were used in this experiment. Animals were divided into two groups, group 1 served as a control and received the corn oil and group 2 was treated with 200 mg/kg body weight (b.w.) of malathion for 30 days. In result, we found that the malathion administration led to the perturbation of biochemical markers and histopathological as well as molecular damages. These changes were accompanied by an oxidative alternation which was evaluated by lipoperoxidation process and MDA production, a diminution of sulfhydril groups (SH) content and an antioxidant enzyme activities depletion such as total superoxide dismutase (SOD) and its isoforms, catalase (CAT) and glutathione peroxidase (GPx) in both kidney and liver tissues. These changes were related with many histopathological lesions in the liver and kidney tissues. More importantly, this insecticide clearly caused a decline in the GPx-4 expression in liver as well as GPx-3 in kidney. These data suggest that prepubertal male mice exposure to malathion showed a marked deregulation of liver and kidney functions.